Practical application of mathematical models of electro-thermo-mechanical processes in industrial induction furnaces with the aim of increasing their energy efficiency - Pachkolin, Yurii; Bondarenko, Alexander; Levchenko, Serhii (Technology audit and production reserves, 2018)
The object of research is an industrial induction steel-melting furnace. One of the most problematic places in induction steel-melting furnaces is low energy efficiency due to their constructive imperfections and the existing technological process of thermal work, which leads to excessive energy consumption. In the course of the study, mathematical modeling of the influence of the electromagnetic field on the elements of an induction furnace was used. Experiments were also carried out to verify the action of the electromagnetic field on the trajectory and speed of movement of the molten metal both in laboratory conditions and in an induction furnace. To study the movement of the molten metal, a special thermal float was manufactured. The float consists of a ceramic heat-resistant sleeve, into which a tungsten rod is inserted. For greater accuracy of the experiment, the float weight is equal to the weight of the melt of the same volume. Thanks to the experiments conducted in the laboratory and on the furnace, an algorithm was developed for the operating modes of the electric inductor. The analysis of the inductor operation modes at different frequencies is carried out. The influence of the frequency of the current supplying the inductor to the penetration depth of the electromagnetic field is revealed. With decreasing current frequency (f <50 Hz), the penetration depth increases and vice versa, with increasing (f> 50 Hz) it decreases. It is also confirmed that the maximum effect of the electromagnetic field on the melt is concentrated inside (along the height) of the melt. The main issues of practical application of the mathematical model of electro-thermo-mechanical processes arising in industrial induction furnaces during heating and melting of various metals and their alloys, which are widely used in mechanical engineering, are considered. The system of equations in the form of boundary-value problems of electrodynamics for a quasi-stationary magnetic field, non-stationary heat conduction and non-isothermal thermoplasticity is used. The practical application of the proposed methods of using the capabilities of mathematical modeling of electrometallurgical processes is the basis for the creation of modern computer programs with the aim of improving energy efficiency by significantly reducing unnecessary, unreasonable energy losses.